Integrating AI into Kanban for Agile Mobile Product Development: Enhancing Workflow Efficiency, Real-Time Monitoring, and Task Prioritization - Kumari, Seema (Journal of Science & Technology, 2023)
The integration of Artificial Intelligence (AI) into Kanban systems has emerged as a transformative approach to enhancing workflow efficiency, real-time monitoring, and task prioritization within Agile mobile product development. This paper aims to systematically investigate the intersection of AI and Kanban methodologies, elucidating how these technologies can synergistically improve the performance and adaptability of Agile teams in dynamic mobile development environments. With the increasing complexity of mobile applications and the rapid pace of technological advancements, traditional Kanban practices may fall short in addressing the nuanced challenges that contemporary development teams face. Hence, this research proposes a novel framework that leverages AI capabilities to augment Kanban practices, thus facilitating more intelligent decision-making processes.
Keywords: Artificial Intelligence; Kanban; Agile methodologies; mobile product development